THE IMPACT OF FISCAL DECENTRALIZATION ON ECONOMIC GROWTH IN THE CEE COUNTRIES - Makreshanska mladenovska, Suzana; Tashevska, Biljana (Varazdin Development and Entrepreneurship Agency, Varazdin, Croatia / University North, Koprivnica, Croatia / Faculty of Management University of Warsaw, Warsaw, Poland / Faculty of Law, Economics and Social Sciences Sale - Mohammed V University in Rabat, Morocco / Polytechnic of Medimurje in Cakovec, Cakovec, Croatia, 2019)
There has been a global trend of public sector decentralization over the last few decades, justified by the fact that transferring public revenues and expenditures from central to local government level is expected to deliver greater public sector efficiency, higher economic growth rates and better overall macroeconomic performance. In this paper, we empirically investigate if fiscal decentralization enhances or hinders economic growth in Central and European (CEE) member countries of the European Union. Using panel data for the period 1992-2012, we try to determine whether fiscal decentralization, measured as the share of local government revenues/expenditures in general government revenues/expenditures has a positive effect on the GDP per capita growth rate. According to our findings, fiscal decentralization has an adverse effect on the economic growth rate in the CEE countries. This is in line with the argument that in developing countries decentralization could fail to deliver the expected positive impulse on growth if certain economic and institutional preconditions are absent. A negative impact is also found to come from the size of the public sector and inflation. On the other hand, the improvement of the fiscal balance and the openness of the economy have a positive impact on growth.
Keywords: CEE countries, Economic growth, Fiscal decentralization